Value of Prognostic Nutritional Index as a Predictor of Lymph Node Metastasis in Gastric Cancer - KOSUGA, TOSHIYUKI; KONISHI, TOMOKI; KUBOTA, TAKESHI; SHODA, KATSUTOSHI; KONISHI, HIROTAKA; SHIOZAKI, ATSUSHI; OKAMOTO, KAZUMA; FUJIWARA, HITOSHI; KUDOU, MICHIHIRO; ARITA, TOMOHIRO; MORIMURA, RYO; MURAYAMA, YASUTOSHI; et al. (Anticancer research, 2019)
This study examined whether the prognostic nutritional index (PNI) is a useful predictor of pathological lymph node metastasis (pN+) in gastric cancer (GC). This study retrospectively examined 167 patients with advanced GC (cT2-T4) undergoing curative gastrectomy. The predictive ability of PNI for pN+ was evaluated in comparison with that of clinical lymph node metastasis (cN+) determined by computed tomography (CT). The optimal cut-off value of PNI for predicting pN+ was 46 according to the receiver operating characteristic curve analysis. Multivariate analysis revealed a PNI<46 [odds ratio (OR)=2.905; 95% confidence interval (CI)=1.347-6.638, p=0.006], cN+ (OR=2.323; 95%CI=1.204-4.579, p=0.012), and undifferentiated-type adenocarcinoma (OR=2.032; 95%CI=1.060-3.947, p=0.033) to be independent predictors of pN+. PNI detected pN+ with a higher specificity (84.9%) and positive predictive value (PPV) (75.6%) than cN+ (68.5% and 68.1%, respectively). When the subjects were limited to patients with cN+, the specificity and PPV of a PNI<46 for pN+ became markedly high (91.3% and 90.5%, respectively). PNI predicts pN+ with a high specificity in patients with a clinical diagnosis of advanced GC; therefore, PNI may aid in the definitive diagnosis of pN+, especially in combination with CT findings.